1990
DOI: 10.1111/j.1749-6632.1990.tb48904.x
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Maturation of the Hippocampus and the Developmental Progression of Children's Performance on the Delayed Non‐Matching to Sample and Visual Paired Comparison Tasksa

Abstract: Although it has been widely speculated that the hippocampus, and the type of memory dependent upon the hippocampus, develops late in primates just as it does in rats (e.g., Nadel & Zola-Morgan, 1984; Bachevalier & Mishkin, 1984; Schacter & Moscovitch, 1984), the evidence to date would not seem to support this. Instead, there is behavioral evidence of very early recognition memory and anatomical evidence of very early hippocampal maturation in human and non-human primates. It is true, however, that the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
131
3
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 86 publications
11
131
3
2
Order By: Relevance
“…For example, Barr et al (1996) found that 6-month-olds exhibited significant deferred imitation after a 24-hr delay if they viewed a demonstration of the target actions for 60 s. In contrast, 12-month-olds could imitate the actions 24 hr later if they viewed the demonstration for only 30 s. Likewise, 6-month-olds required a response period of 120 s to imitate the modeled actions, whereas 12-montholds required a response period of only 90 s to do so. Diamond (1990) found that increasingly older infants required progressively less time to encode a stimulus in a visual paired-comparison task, and Colombo and Mitchell (1990) reported that increasingly older infants spent progressively less time looking at the target, but solved visual discrimination tasks with increasingly greater success.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Barr et al (1996) found that 6-month-olds exhibited significant deferred imitation after a 24-hr delay if they viewed a demonstration of the target actions for 60 s. In contrast, 12-month-olds could imitate the actions 24 hr later if they viewed the demonstration for only 30 s. Likewise, 6-month-olds required a response period of 120 s to imitate the modeled actions, whereas 12-montholds required a response period of only 90 s to do so. Diamond (1990) found that increasingly older infants required progressively less time to encode a stimulus in a visual paired-comparison task, and Colombo and Mitchell (1990) reported that increasingly older infants spent progressively less time looking at the target, but solved visual discrimination tasks with increasingly greater success.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, immature cognition is characterized by greater susceptibility to interference from competing actions (Diamond, 1990;Brainerd and Reyna, 1993;Dempster, 1993;Casey et al, 2001Casey et al, , 2002Munakata and Yerys, 2001), as evidenced in children when performing Stroopinterference tasks (Tipper et al, 1989), card sorting (Zelazo et al, 1996;Munakata and Yerys 2001), and go-no-go tasks (Luria, 1961; Casey et al, 1997a,b;Vaidya et al, 1998). In all cases, children have more difficulty making the correct response when there is interference from competing response alternatives.…”
Section: Abstract: Development; Basal Ganglia; Hippocampus; Imaging;mentioning
confidence: 99%
“…Lesion studies in monkeys have identified a number of tasks that are heavily dependent on various areas of prefrontal cortex, including DR, A not B, DA, and DMTS and DNMTS (300)(301)(302). Both infant humans and infant monkeys develop the ability to perform these tasks relatively late: over the course of the first year of life in monkeys (303,304) and over the first 3 years or so in humans (305,306) (308). In humans, the volume of the hippocampus is fully mature at 15 months, whereas the PFC does not reach adult volume until 10 years of age.…”
Section: Assessment Of Nervous System Function In Animals and Humansmentioning
confidence: 99%